2012
DOI: 10.1088/0031-9155/57/8/2251
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of methods for quantification of rCBF using high-resolution [15O]H2O PET images

Abstract: This study aimed to derive accurate estimates of regional cerebral blood flow (rCBF) from noisy dynamic [¹⁵O]H₂O PET images acquired on the high-resolution research tomograph, while retaining as much as possible the high spatial resolution of this brain scanner (2-3 mm) in parametric maps of rCBF. The PET autoradiographic method and generalized linear least-squares (GLLS), with fixed or extended to include spatially variable estimates of the dispersion of the measured input function, were compared to nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…These values are in line with the recent data acquired on an HRRT by Walker and co-workers [17], who found values of 0.44 and 0.15 mL/cm 3 per minute (Table 3). The good correlation between BFM and NLR results implies that this linearization is a valid approach.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These values are in line with the recent data acquired on an HRRT by Walker and co-workers [17], who found values of 0.44 and 0.15 mL/cm 3 per minute (Table 3). The good correlation between BFM and NLR results implies that this linearization is a valid approach.…”
Section: Discussionsupporting
confidence: 92%
“…Total gray and white matter CBFs were 0.35 ± 0.05 and 0.25 ± 0.04 mL/cm 3 per minute, respectively, (GM:WM = 1.4). Table 3 shows CBF values obtained from the manually drawn gray and white matter regions (ratio GM/WM = 3.3) as well as a comparison with literature data, recently obtained using another HRRT scanner [17]. Figure 4 shows the relationship between CBF values derived from BFM and NLR analyses on smoothed data.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Next, fully corrected sinograms were reconstructed using the standard 3D OP-OSEM reconstruction algorithm (3133), resulting in 207 image planes with 256 × 256 voxels and a voxel size of 1.22 × 1.22 × 1.22 mm 3 . The effective spatial resolution of the reconstructed images was 3 mm full-width at half maximum.…”
Section: Methodsmentioning
confidence: 99%
“…As the use of TOF PET receded in the late 1980s and as iterative approaches became routine clinical tools due to their improved contrast-vs.-noise trade-offs and better visual quality, analytic (non-TOF) algorithms have lately been used only for specialized quantitative studies and as a gold standard for comparative studies evaluating the biases of reconstruction approaches (Blinder et al , 2012; Reilhac et al , 2008; van Velden et al , 2008; Badawi et al , 1999; van Velden et al , 2009; Verhaeghe et al , 2010; Walker et al , 2011; Walker et al , 2012); analytic reconstructions are also used for intrinsic spatial resolution characterization of PET scanners (NEMA Standards Publication NU 2-2001NEMA Standards Publication NU 2-2001). With the renewed interest in TOF PET, analytic TOF methods have been revisited, and several algorithms have been studied (Cho et al , 2008; Conti et al , 2005; Kao, 2008; Watson, 2007), with improved noise characteristics reported (Watson, 2007, 2008).…”
Section: Introductionmentioning
confidence: 99%